The british experience regarding the defence of competition - Howe, Martin; Office of Fair Trading (Revista do IBRAC, 2025)
It is an honour to be invited to this Seminar to share with you some of our experience in the United Kingdom in the field of competition policy. That experience, which now extends over nearly 50 years, has been forged in a well developed market economy. I am very conscious that your own situation here in Brazil is very different as are your laws, institutions and traditions.